MDM2 inhibitors: Targeting p53-MDM2 interaction to anti-cancer - Zhang Xulin (E3S Web of Conferences, 2021)
P53 is a recognized tumor suppressor gene, which mainly depends on the activity of its transfer factor to realize the tumor suppressor effect. Mouse two-minute 2 (MDM2) is an important inhibitor of p53. When combined with MDM2, the activity of p53 will be reduced, and the anti-cancer effect will be weakened. According to the mechanism between p53 and MDM2, researchers focus on the inhibitors to inhibit their binding. Through a large number of drug screening methods and means, this article has found many new inhibitors of p53-MDM2 interaction, most of which are still in the clinical research stage. Specifically, we classify the drugs based on their different action mechanisms. Firstly, some drugs combine with MDM2 to inhibit the p53-MDM2 interaction. They are Siremadlin (NVP-HDM201), RG7112, and NVP-CGM09. While some act on p53, they rely on their induction of p53 signalling and inhibition of tumour cell proliferation in p53 wild-type tumor cell lines, like MK-8242 and KRT-232(AMG-232). What’s more, one inhibitor’s action bases on P53 and MDM2 in T cells is APG-115. And last but not least, there are also several drugs that stable tumor suppressor TP53, leading to p53 activation and inducing cell cycle arrest and apoptosis, they are Idasanutlin (RG7388) and Milademetan (DS-3032/RAIN-32). Furthermore, clinical studies are finding that monotherapy does not deliver a powerful therapeutic effect. Various combination strategies are being explored with MDM2 inhibitors preclinically and in the clinic. This article will talk about some specific combinations: APG-115 combine with immune checkpoint inhibitor PD-1/PD-L1, MDM2 inhibitors combine with BCL-2 inhibitors, anti-CD20 therapeutic antibodies, and the last, combine with alkylating agents.